Karakteristik Transmisi Gelombang Ultrasonik dan Hubungannya dengan Sifat Fisiko-Kimia Buah Naga - Siti Djamila; I Wayan Budiastra; Sutrisno . (PERTETA, 2010)
AbstractCommonly the quality of dragon fruit in Indonesia is determined manually by using visual appearances and it gives un-uniformly results caused by human factors and the judgement is not reflected the internal quality of dragon fruit. Destructive method is usually used to determine the internal quality of dragon fruit that is unsuitable for quality control of fresh dragon fruit. So a non destructive method is required for evaluation the quality of dragon fruit. The objectives of the research were to determine the physico-chemical and ultrasound wave transmission characteristics of super red dragon fruit according to harvesting time, and to study the relationship between ultrasound wave transmission characteristics and physico-chemical characteristics of super red dragon fruit. Super-red dragon fruits were harvested at 30, 32, and 34 days after flower blooms (150 samples) from PT Wahana Cory, Ciapus, Bogor. The results showed that the ultrasound velocity of super red dragon fruit ranged from 614.10 to 680.16 m/s and the attenuation coefficient were 57.32 to 62.40 Neper per meter. The attenuation coefficient was significantly different according to maturity. There were significant correlations between ultrasound parameters (velocity and attenuation coefficient) and physico-chemical of super red dragon fruit (firmness, sugar content, total soluble solid, and total acid).Keyword: dragon fruit, attenuation, ultrasound, velocity Diterima: 25 September 2009; Disetujui: 3 Februari 2010